SIFAT CAMPURAN BERASPAL PANAS DENGAN ASBUTON BUTIR - Furqon Affandi (Jurnal Jalan-Jembatan, 2009)
One of the asbuton products that frequently used for hot mix asphalt is granular asbuton with maximum size of 2,36 mm. The amount of granular asbuton used in asphalt mix is approximately between 5% to 10% of aggregate by weight. The assumption used in mix design is bitumen from granular asbuton can be all removed from its mineral matter and become soft and blended with petroleum bitumen, so that it can partly substitute asphalt in mixture. In addition, another assumption is asbuton mineral can be uniformly mixed with aggregate. The fact that in the mixture, bitumen from asbut on can not remove from its mineral matter. As a consequence, in actual implementation, there is different volumetric calculation of mixture.Therefore, mix gradation correction is required as a result of a major difference in unit weight of asbuton and aggregate, and the size of asbuton and its mineral. Hot mix asphalt with granular asbuton has high stiffness, high resistance to deformation, however, it has low resistance to cohesion and stripping, shorter fatigue life, more sensitive to increasing of stress/strain, more brittle, compared with the mixture using petroleum bitumen 60 pen grade. Key words : Granular asbuton, hot mix asphalt, volumetric of mixes, stiffness, fatigue